ANALISIS PERBANDINGAN PENGGUNAAN METODE PENYUSUTAN AKTIVA TETAP BERDASARKAN KEBIJAKAN AKUNTANSI DAN PAJAK PADA PROFITABILITAS PT. WIJAYA KARYA (PERSERO) TBK. - Puspa Rini (Mediastima, 2020)
There are differences in the provisions according to the statement of Financial accounting standards with the provisions of the Constitution on which regulates the management of fixed assets to determine the amount of depreciation load of fixed assets so that the profit can be achieved by the company of different methods and provisions and can be known to the ability level of the company in generating profitability. This research was conducted to understand the difference in the use of depreciation methods in fixed assets according to accounting and tax policies in creating company profitability. Based on research that has been carried out depreciation expense based on greater accounting policy compared to depreciation load using depreciation method based on tax policy. Resulting in a different profit. This results in a profitability ratio that fluctuates each of its periods.